RADIKALISME AGAMA: REKONSTRUKSI PENAFSIRAN JIHAD DAN ISLAM YANG RAHMAT LIL ‘ALAMIN - Maulana Maulana (CV. Adiba Aisha Amira, 2022)
This paper describes radicalism or the notion of a sect that wants social and political change or reform by means of violence, an understanding that refers to certain groups, who want and make changes to religious values ​​that are considered contrary to their understanding. Among the ideologies they profess is to disbelieve all those who commit immorality, those in power who do not follow Allah's law, to disbelieve in the clergy and ordinary people who have different views, to disbelieve in those who accept their thoughts but are reluctant to become followers and are reluctant to make promises (pledges) of allegiance to them. The priest, as for if the congregation leaves the group then it is considered apostate. Understand radicalism or extremism which most experts call the puritans, jihadists. Such understanding does not exist without the underlying causes. The underlying factors are: unemployment and poverty, munkar and polytheism, understanding wrong religious teachings, not understanding the rules of maslahah and mafsadah, unstable political and security conditions, ignorance, being less selective in absorbing information, excessive religious enthusiasm, following lust and leave the scholars and jihad out of their mission.